Evaluation of Breast Cancer (BC) Awareness among Female University Students in Zarqa University, Jordan - Ashraf Kan'an (European Journal of Breast Health, 2018)

(untitled)
Objective: The purposes of this study were to assess the level of Breast Cancer (BC) awareness of Jordanian female university students, measure their attitudes toward BC treatment, and compare the level of awareness and attitudes of students in the science and humanities faculties.Materials and Methods: The current study was cross-sectional and conducted among female students in Zarqa University in Jordan. Stratified random sampling and simple random sampling were employed to select the colleges and the students, respectively. The sample size was 326 students. Data was collected and analyzed by self-administered questionnaire and SPSS version 23.0, respectively.Results:The number (proportion) of university students who had poor levels of awareness of BC, general knowledge about BC scale, knowledge about BC symptoms scale, and knowledge about risk factors of BC scale were was 270 (83%), 166 (51%), 182 (56%) and 292 (90%), respectively. Also, 92 (28%) students and 234 (72%) students had high and medium attitudes toward BC treatment, respectively. There were significant differences between the humanities and science faculties students’ awareness about BC and their attitudes toward BC treatment (p<0.05). Also, the results revealed that the students’ main information source about BC was mainly health-care professionals, followed by internet and television.Conclusion: The current status of awareness of BC among Jordanian female students and their attitudes toward BC treatment are insufficient. Therefore, university compulsory courses need to be modified to include BC topics and promote awareness about BC.